The interferon-stimulated gene product oligoadenylate synthetase-like protein enhances replication of Kaposi's sarcoma-associated herpesvirus (KSHV) and interacts with the KSHV ORF20 protein. - Kendra A Bussey; Ulrike Lau; Sophie Schumann; Antonio Gallo; Lisa Osbelt; Markus Stempel; Christine Arnold; Josef Wissing; Hans Henrik Gad; Rune Hartmann; Wolfram Brune; Lothar Jänsch; et al. (PLoS Pathogens, 2018)
Kaposi's sarcoma-associated herpesvirus (KSHV) is one of the few oncogenic human viruses known to date. Its large genome encodes more than 85 proteins and includes both unique viral proteins as well as proteins conserved amongst herpesviruses. KSHV ORF20 is a member of the herpesviral core UL24 family, but the function of ORF20 and its role in the viral life cycle is not well understood. ORF20 encodes three largely uncharacterized isoforms, which we found were localized predominantly in the nuclei and nucleoli. Quantitative affinity purification coupled to mass spectrometry (q-AP-MS) identified numerous specific interacting partners of ORF20, including ribosomal proteins and the interferon-stimulated gene product (ISG) oligoadenylate synthetase-like protein (OASL). Both endogenous and transiently transfected OASL co-immunoprecipitated with ORF20, and this interaction was conserved among all ORF20 isoforms and multiple ORF20 homologs of the UL24 family in other herpesviruses. Characterization of OASL interacting partners by q-AP-MS identified a very similar interactome to that of ORF20. Both ORF20 and OASL copurified with 40S and 60S ribosomal subunits, and when they were co-expressed, they associated with polysomes. Although ORF20 did not have a global effect on translation, ORF20 enhanced RIG-I induced expression of endogenous OASL in an IRF3-dependent but IFNAR-independent manner. OASL has been characterized as an ISG with antiviral activity against some viruses, but its role for gammaherpesviruses was unknown. We show that OASL and ORF20 mRNA expression were induced early after reactivation of latently infected HuARLT-rKSHV.219 cells. Intriguingly, we found that OASL enhanced infection of KSHV. During infection with a KSHV ORF20stop mutant, however, OASL-dependent enhancement of infectivity was lost. Our data have characterized the interaction of ORF20 with OASL and suggest ORF20 usurps the function of OASL to benefit KSHV infection.